Transcultural Appropriation оf Shakespeare in the 19th Century Serbia - Zorica Bečanović Nikolić (Књижевна историја, 2024)
This article examines a specific and unusual instance of the 19th century bardolatry in Serbia. Its focus is on the inter-textual and poetic qualities of celebratory parody as well as on the politically engaged dialogue with Shakespeare in the narrative poem On Shakespeare’s Tercentenary, written by the Serbian romantic poet Laza Kostić in 1864. The argument of the essay is that Laza Kostić authored an original contribution to the 19th century Romantic European admiration of Shakespeare, expressing, at the same time, indebtedness to the German reception of Shakespeare on the one hand, and frustration of a Slavic culture experiencing a strong German cultural influence on the other. This particular East European appropriation of Shakespeare thus forms a transcultural triangle, including English and German centers of cultural dissemination, and an engaged response to them from the Slavic margins of Europe. The vast distance from the Serbian people, whose position could be interpreted as mutatis mutandis ‘subaltern’, to Shakespeare, glorified by the entire world, seems to be traversed by the aesthetic reception and cultural appropriation carried out by Kostić and his likes. In this transcultural exchange, Shakespeare appears as a trustworthy collocutor, with whom, in a ‘presentist’ manner avant la lettre, the Serbian poet discusses his own political and cultural dilemmas. Laza Kostić appears as a sophisticated and original bardolator and, at the same time, mediator between Shakespeare and the Serbian ‘subalternity’.